2019
DOI: 10.1093/jisesa/iez108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Honey (Apis dorsata [Hymenoptera: Apidae]) on Larval Growth and Silk Cocoon Yield of Bombyx mori (Lepidoptera: Bombycidae)

Abstract: The present study was carried out to determine the influence of 2% aqueous honey (Apis dorsata Fabricius, 1793 [Hymenoptera: Apidae]) on larval growth and silk cocoon yield of fifth-instar larvae of the silkworm, Bombyx mori (Linnaeus, 1758) (Lepidoptera: Bombycidae). The larvae of silkworms (Chinese HUAKAND2) were divided into a control and an experimental groups (n = 20 in each group). Control group was fed with plain mulberry leaves throughout the fifth instar, whereas the experimental group was offered mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Nevertheless, after days 3, 5 and 7, differences could be observed between the two groups. Specifically, the experimental group left fewer uneaten leaves than the control group, suggesting that Bombyx mori has a predisposition for eating honey-enhanced leaves [30].…”
Section: The Impact Of Honey On Bombyx Mori Biological and Technological Traitsmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, after days 3, 5 and 7, differences could be observed between the two groups. Specifically, the experimental group left fewer uneaten leaves than the control group, suggesting that Bombyx mori has a predisposition for eating honey-enhanced leaves [30].…”
Section: The Impact Of Honey On Bombyx Mori Biological and Technological Traitsmentioning
confidence: 91%
“…The treatment was applied for 4 days. Specifically, the larvae of silkworms received honey-dipped mulberry leaves on days 1, 3, 5 and 7, and on days 2, 4, 6 and 8, they received just mulberry leaves [30]. Surprisingly, in the first instance, after day 1, the silkworms included in the experimental group did not consume more mulberry leaves than the control group.…”
Section: The Impact Of Honey On Bombyx Mori Biological and Technological Traitsmentioning
confidence: 95%
See 1 more Smart Citation
“…The artificial diet of silkworms generally comprises mulberry leaf powder, defatted soybean powder, corn powder, mulberry green branch powder, cellulose, molding agents, vitamins, preservatives, and inorganic salt, which can adapt to the feeding characteristics of silkworms and meet the nutritional needs of silkworms. Currently, most of the improvements are aimed at improving the nutritional composition of the artificial diet ( Saviane et al 2014 , Shifa 2016 , Bhatti et al 2019 ). Shifa (2016) found that supplementation of 10% Zea mays flour significantly increases silkworm larval weight, cocoon weight, and cocoon shell weight compared to controls ( Shifa 2016 ).…”
mentioning
confidence: 99%
“…Shifa (2016) found that supplementation of 10% Zea mays flour significantly increases silkworm larval weight, cocoon weight, and cocoon shell weight compared to controls ( Shifa 2016 ). Additionally, Bhatti et al (2019) found that adding 2% aqueous honey enhances larval growth and the silk cocoon yield ( Bhatti et al 2019 ).…”
mentioning
confidence: 99%